Effect of fertilisation timing on the partitioning of foliar‐applied nitrogen in Vitis vinifera cv. Chasselas: a 15N labelling approach. (20th January 2015) - Verdenal, T.; Spangenberg, J.E.; Zufferey, V.; Lorenzini, F.; Spring, J.‐L.; Viret, O.
Abstract Background and Aims Yeast assimilable nitrogen (YAN) in grape must is an important determinant of wine composition. The effect of foliar nitrogen fertilisation on YAN concentration in must of Vitis vinifera L. cv. Chasselas was studied. Nitrogen assimilation and translocation were investigated by applying 15N‐labelled urea at flowering and at veraison. Methods and Results Foliar urea was applied on field‐grown Chasselas grapevines using labelled (10 atom% 15N) and unlabelled urea. The vines were excavated at harvest, and plant parts were separated and analysed. Thus, the distribution of dry organic matter and of total organic carbon and total organic nitrogen in the plant at harvest was determined. Bunches were the strongest N sink among all of the organs during both fertilisation periods. The highest YAN in the must, however, was obtained when the urea was applied during veraison. Conclusions Isotope labelling was used to describe N partitioning throughout the vine in response to foliar nitrogen fertilisation with urea at flowering and at veraison. Differences between organs in carbon and nitrogen isotope discrimination at natural abundance were established. Fertilisation with urea during veraison increased the YAN concentration in Chasselas grape must. Significance of the Study Results show that it is more effective to correct YAN deficiency in the vineyard with application of foliar urea during veraison than during flowering.